Bed, Breakfast and Friendship: Intimacy and Distance in Small-Scale Hospitality Businesses - Johan Hultman; Erika Andersson Cederholm (Culture Unbound: Journal of Current Cultural Research, 2010)
Through an analysis of the narrative of a Bed and Breakfast (B & B) and art gal-lery owner, the emergence of intimacy as a commercial value in the hospitality industry is illustrated. This is a formation of economic value where economic ra-tionality as a motive for commercial activity is rejected. Simultaneously though, a different set of market attitudes are performed by hospitality practitioners in the course of everyday interactions with customers, and a tension between emotional, spatial and temporal intimacy and distance is uncovered and discussed. It is con-cluded that commercial friendship is a more complex issue than what has been acknowledged so far in the hospitality literature. A continued discussion of inti-macy in hospitality will therefore affect the cultural understanding of emotions, identity and lifestyle values on the one hand, and business strategy, value creation and markets on the other.